Modelling of Solar Power Generation Systems as a Source of Agricultural Irrigation Pumps - I Ketut Parti; Ni Wayan Rasmini; I Nyoman Mudiana; I Made Purbhawa (Jurnal Penelitian Pendidikan IPA, 2023)
New and renewable energy (EBT) is a green energy generator because its supply is abundant and will not run out all the time. Renewable energy is clean energy and does not produce pollution because it is not from fossil fuels such as natural gas, and it will not damage the environment on earth. One of the green energy generators is the Solar Power Plant (PLTS), one of the green energies developed by the Indonesian government to replace energy derived from fossil fuels. The government has set a National Energy Policy, targeting the contribution of NRE to the national energy mix by 2025 is 17% (Perpres No. 5/2006), amended by PP No.79/2014, 23% (2025, (31) % (2050) To be able to support this, it is hoped that a study and research will be carried out, "Modeling of solar power generation systems as a source of agricultural irrigation pumpsâ€ with research that can obtain results that can be obtained irrigating rice fields in Subak Kanca Tegeh, Selan Bawak Village, Tabanan Regency so that farmers who are having rice fields that cannot drain water can be supplied with water by installing a pump 10 ha from 50 ha, the existing water has not been able to reach this far with a higher topography, it is necessary to plan how much power is needed so that the water pump can obtain enough energy to the pump can work normally.